Under the dome. Season 1 [videorecording (DVD)] - Vaughan, Brian K.; Vogel, Mike; Lefevre, Rachelle; Norris, Dean; Martinez, Natalie; King, Stephen, 1947- (Under the dome ;)
The small town of Chester's Mill is suddenly and inexplicably sealed off from the rest of the world by a massive transparent barrier. The epic story of a town in peril unfolds as the residents struggle to maintain control and ultimately figure out the truth about the dome.